Consistency of group key exchange protocols - CAO Chun-jie1; MA Jian-feng1; GUO Yuan-bo2 (Tongxin xuebao)
The consistency is a basic security requirement,but it is much trickier and many times overlooked. By care-fully analyzed to several famous were found provably-secure group key exchange protocols at present,different attacks of the consistency to these protocols were found respectively. These attacks will result in that all the members have different view of peers’ identities and destroying the integrity of the current group. Furthermore,improvements to overcome the security vulnerabilities of these protocols were proposed.